The Influence of Motivation, Work Environment, Well-Being, Career, and Organizational Culture on Work-Life Balance : English - Annisa Farah Tadayyana Wa Mutsaqqof; Suyoto (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of motivation, work environment, well-being, career, and organizational culture on employee work-life balance at PT Bank Rakyat Indonesia (Persero) Tbk. This study used a quantitative approach with SEM-PLS analysis techniques. The sample consisted of 220 respondents using the Slovin formulation. The results indicate that motivation, well-being, and organizational culture do not significantly influence work-life balance. However, the work environment and career variables significantly influence work-life balance. This confirms that both internal and external organizational factors play a crucial role in maintaining employee work-life balance in the stressful banking sector. This study provides theoretical contributions to the development of human resource management studies, particularly regarding the application of Self-Determination Theory in the context of work-life balance. Practically, the research findings can serve as recommendations for BRI management in designing work strategies that support employee well-being and retention.This study highlights the phenomenon of work-life balance in the Indonesian banking sector by simultaneously integrating five key variables, thus providing a comprehensive perspective for organizational policy development.